First report of a persistent oropharyngeal infection of type 2 vaccine-derived poliovirus (iVDPV2) in a primary immune deficient (PID) patient after eradication of wild type 2 poliovirus. (June 2019) - Weil, Merav; Rahav, Galia; Somech, Raz; Stauber, Tali; Alfandari, Jacqueline; Weiss, Leah; Silberstein, Ilana; Indenbaum, Victoria; Or, Itay Bar; Mendelson, Ella; Sofer, Danit; Shulman, Lester M.
Highlights: Persistent poliovirus infections occur in primary immune deficient patients. Type 2 poliovirus was isolated from throat swabs and stools of such a patient. Genetic analysis revealed that the type 2 polioviruses were vaccine-derived iVDPV2s. Poliovirus evolved independently in throat and gut during persistence. iVDPV2 excretion continued after global withdrawal of live type 2 polio vaccine. Abstract: This is the first report of persistent oropharyngeal mucosal infection with type 2 poliovirus (iVDPV2) in a primary immune deficient patient (PID) after wild type 2 poliovirus eradication. The iVDPV2 also established persistence in the gut. iVDPV2 at both loci evolved independently. Persistent oral infections present a potential risk for oral-oral as well as fecal-oral poliovirus transmission during transition to a poliovirus 2-free world.